The assemblage structure of large size sea urchins (Diadematidae) in Northern Vietnam - Do Hung Dang, Viet; Nozawa, Yoko; Van Chien, Pham; Dinh Do, Thinh; Van Quang, Pham; Van Hung, Tran; Manh Hung, Vu; Tran Manh, Ha; Nguyen Duc, The; Dam Duc, Tien (Vietnam Journal of Marine Science and Technology, 2022)
The large sea urchins (Diadematidae) are widely distributed worldwide, from temperate to tropical waters. Diadematidae is an important herbivore in the coral reef ecosystem through herbivore-algal-coral interaction, which maintains the reef’s health. Many studies of Diadematidae have been performed around world, but in Vietnam, there is little known about the ecology of this group. Here, we first investigated the assemblage structure of Diadematidae in Northern Vietnam. We observed 43 sites of representative coral reefs in Ba Mun - Co To, Cat Ba - Ha Long, and Hon Me. Based on the surveys, we found four species of considerable size sea urchins, of which the most common species is Diadema setosum (79.8% of the total), Enchinothrix calamaris (10.1%), E. diadema (8.3%), and D. savignyi (1.8%). Among three study regions, Hon Me is the most diverse. In addition, Hon Me also has the highest density of sea urchins. However, this value is generally low compared to that in Southern Vietnam and other neighboring countries. Further study is needed to investigate the ecology and reproductive biology of Diadematidae to provide fundamental information for sustainable exploitation and conservation.